Penerapan Model Blended Learning Dalam Pembelajaran Pendidikan Kewarganegaraan Untuk Membentuk Karakter Wirausaha - Sitirahia Hi. Umar; Wahyudin Noe (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2022)
Entrepreneurship education through learning Civics Education can foster the entrepreneurial character of students from an early age. In general, this research aims to obtain descriptive information regarding the application of the blended learning model in Civics learning to build the entrepreneurial character of students at SMA Negeri 4 Kota Ternate. This research uses a qualitative approach with a case study method. The results illustrate that the application of the blended learning model in Civics learning at SMA Negeri 4 Kota Ternate can build the entrepreneurial character of students because: 1) availability of Information and Technology (IT) facilities in the classroom (such as projectors, laptops and smartphones) that are sufficient to support blended learning in an interesting, creative and innovative way; 2) the application of the blended learning model in Civics learning can optimize the formation of mindsets, explore interests and talents, and learner independence in entrepreneurship. In the future, this research can be further developed by creating an entrepreneurship learning model based on local wisdom so that it is able to develop students' entrepreneurial character well.